2018
DOI: 10.1093/mnras/sty3304
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable change of the spectrum of the magnetic Of?p star HD 148937 reveals evidence of an eccentric, high-mass binary

Abstract: We report new spectroscopic observations of the magnetic Of?p star HD 148937 obtained since 2015 that differ qualitatively from its extensive historical record of weak, periodic spectral variations. This remarkable behaviour represents clear evidence for an unprecedented change in the character of variability of the star. In this paper we describe the new spectral properties and compare them to the previous line profiles. Based on measurements of the radial velocities of the C iii/N iii emission lines near 464… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…In respect to the possible binary nature of HD 54879, it was suggested in recent years that three out of five Of?p stars are members of binary systems. Long-term radial velocity changes indicating binarity were reported for the Of?p star HD 191612 (Howarth et al 2007) who suggested P orb = 1542 d. According to Wade et al (2019), the Of?p star HD 148937 is likely a high-mass, double-lined spectroscopic binary (Wade et al 2019). Also for the Of?p star HD 108 Naze et al (2008) reported that a very long-term binary cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…In respect to the possible binary nature of HD 54879, it was suggested in recent years that three out of five Of?p stars are members of binary systems. Long-term radial velocity changes indicating binarity were reported for the Of?p star HD 191612 (Howarth et al 2007) who suggested P orb = 1542 d. According to Wade et al (2019), the Of?p star HD 148937 is likely a high-mass, double-lined spectroscopic binary (Wade et al 2019). Also for the Of?p star HD 108 Naze et al (2008) reported that a very long-term binary cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…This may reflect an incomplete characterization of the sample of magnetic O-type stars. Many such systems have been found to be spectroscopic binaries, leading to an increase in the inferred surface magnetic field strength (e.g., ζ Ori Aa and HD 148937; Blazère et al 2015;Wade et al 2019); B d is still a lower limit for the extremely slow rotator HD 108 (Shultz & Wade 2017); and while magnetic fields have still not been detected in the magellanic cloud Of?p stars (Walborn et al 2015;Bagnulo et al 2017), preliminary models of their magnetospheric variability suggest the mean B d of this population to be about 7 kG (Munoz et al 2018), consistent with that of the Galactic magnetic AB stars.…”
Section: Dipolar Magnetic Field Strengthsmentioning
confidence: 99%
“…In the best cases, these systems offer dynamical mass and radius estimates to better than one per cent (Torres et al 2010). Such precise measurements combined with the powerful constrains of co-evolution and identical initial chemical composition have allowed the thorough investigation of the importance of rotation in stellar evolutionary theory (Brott et al 2011a,b;Ekström et al 2012Ekström et al , 2018de Mink et al 2013;Schneider et al 2014), the calibration of pre-through post-main-sequence evolution (Torres et al 2013;Higl & Weiss 2017;Beck et al 2018a;Kirkby-Kent et al 2018), the critical investigation of magnetic fields in stars (Takata et al 2012;Grunhut et al 2013;Torres et al 2014b;Pablo et al 2015;Kochukhov et al 2018;Wade et al 2019), the calibration of distances (Guinan et al 1998;Ribas et al 2000aRibas et al , 2005Hensberge et al 2000;Bonanos et al 2006;Pietrzyński et al 2013;Gallenne et al 2016;Suchomska et al 2019), the investigation of abundances and rotational velocities (Pavlovski & Hensberge 2005;Pavlovski & Southworth 2009;Pavlovski et al , 2018Simón-Díaz et al 2017), and the calibration of asteroseismic modelling (De Cat et al 2000, 2004; Aerts & Harmanec 2004;Schmid et al 2015;Schmid & Aerts 2016;Beck et al 2018a,b;Johnston et al 2019). Additionally, the development of such precise measurements has led to the reported systematic discrepancy between masses obtained via dynamics or empirical spectral relations and fitting theoretically calculated evolutionary tracks…”
Section: Introductionmentioning
confidence: 99%